Strategy of Boarding School (Pesantren) Education in Dealing With the Covid-19 Pandemic - Prasetyo, Muhammad Anggung Manumanoso; Bashori, Bashori; Lailisna, Novi Nur (Khalifa Journal of Islamic Education, 2020)
This study aims to analyze the strategies and roles of Islamic boarding schools in achieving educational programs amidst the threat of the spread of the Covid-19 epidemic. This research uses qualitative research with a case study research approach. The research was conducted at the Pesantren Border Aceh Tenggara as one of the pesantren assisted by the Aceh Province Islamic Boarding School Education Office. The results showed that the strategic management process carried out by the pesantren consisted of three interrelated processes, namely the formulation process, the implementation process (execution), and the strategic process (control). The last process is needed to provide input (feedback) for the next management process. The results of this study have implications for strategic management in pesantren management, namely: 1) the pesantren has managed to survive and strived to achieve the set academic program targets; 2) Islamic boarding schools as covid-19 prevention facilitators at the entrance to the provincial borders as a central place for health checks for immigrants who enter through the borders of Aceh province; 3) transformation of the learning system from traditional models to technology-based learning; and 4) the community is able to objectively assess educational institutions that are good in terms of management so as to allow a clear relationship between rewards and performance.